The Correlation Between Flipped Classroom Implementation and EFL Students' Learning Motivation in an Indonesian Senior High School - sa'diyah, S Aminatus; Sofeny, Daniar; Irmayani, Irmayani (Lembaga Teewan Journal Solutions, 2026)
Learning motivation is a fundamental factor impacting students' engagement and success in learning English as a foreign language (EFL). The flipped classroom has emerged as a student-centered instructional approach that coordinates pre-class learning with interactive classroom exercises to foster active engagement and learner independence. This study aimed to examine the relationship between the usage of the flipped classroom strategy and students' motivation in learning English among twelfth-grade students at SMA Negeri 1 Sukodadi, Indonesia. A quantitative correlational design was utilized, including 40 students chosen through purposive sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics and Pearson Product-Moment Correlation. The findings revealed a strong positive and statistically significant relationship between the usage of the flipped classroom strategy and students' learning motivation (r = 0.742, p < 0.001). These findings show that students who experienced better implementation of the flipped classroom tended to illustrate higher levels of motivation in learning English. This study contributes observational evidence supporting the use of technology-enhanced, student-centered learning to cultivate students' motivation in Indonesian EFL classrooms and recommends that the flipped classroom may serve as a compelling guideline technique for English language teaching.